Interplay Among Perceived Advertisement Impact, Environmental Values, and Solar Product Purchase Intention - Thakur, Anand; Bansal, Ishita; Singla, Kamini (Indian Journal of Marketing, 2025)
Purpose : India has asserted its leadership in the global effort against climate change and sustainable development, with the government dedicated to promoting solar power as the predominant energy source. Effective marketing strategies have historically played a pivotal role in influencing consumer purchase decisions. This study investigated how advertisements influenced customers’ environmental values and intent to purchase solar energy products. Methodology : The research employed covariance-based structural equation modeling to analyze the proposed relationships in the theoretical framework. Data were gathered from 266 potential users of solar energy products. Findings : The study findings indicated that informative advertisements significantly impacted environmental values. Purchase intentions were influenced by informative content in advertisements, brand reinforcement, and stimulation. Additionally, the research confirmed a direct and significant relationship between environmental values and purchase intentions toward solar energy products. Practical Implications : Marketers should craft informative advertisements that highlight the sustainability benefits of solar energy products. Aligning these messages with consumers’ environmental values can significantly enhance purchase intention for solar energy products, reinforcing brand identity and fostering long-term consumer loyalty in the competitive renewable energy market. Originality : This research analyzed how advertising influences consumer environmental values and purchase intentions for solar energy products in India. It emphasized the importance of relevant content in advertisements for enhancing environmental values and encouraging sustainable consumption behaviors in the energy sector.